Cattle identification and traceability: implications for United States beef exports - Schroeder, Ted C.; Tonsor, Glynn T. (Kansas State University Dept. of Agricultural Economics, 2011)
Animal identification (ID) and traceability systems have rapidly developed around the world. Major beef export countries have created animal traceability systems to better protect animal health and to enhance export market growth. Increasingly, beef importing countries are also adopting animal traceability systems for their domestic production, and such systems are evolving as requirements for access to these markets. International animal health, food safety, and world trade associations have all widely recognized the value of effective animal traceability systems. The United States significantly lags in the adoption of emerging world standards for cattle ID and traceability. As such, the United States faces new challenges to maintain and expand beef exports. This fact sheet summarizes developments in global cattle ID and traceability with a focus on assessing the strategic position of the United States relative to major competitors.
Keywords: U.S. beef exports; Food safety; Cattle traceability; Animal identification (ID)